A simple laboratory method for the generation of mixed brominated-chlorinated paraffin single chain mixtures - Walter Vetter; Clara Hägele; Karin Herrmann; Tobias Schulz; Sina Schweizer (Emerging Contaminants, 2024)
Brominated-chlorinated paraffins (Br-CPs) are a comparably new compound class that features both Cl and Br atoms on one or several alkane backbones. Due to legal restrictions in the use of conventional chlorinated paraffins (CPs), Br-CPs have the potential to become emerging contaminants. Currently, their determination is hampered by the lack of suitable reference standards. Here, we present a simple synthesis procedure with single chain alkanes that leads to Br-CPs with ∼4–8 chlorine and 1 to 4 bromine substituents according to gas chromatography with electron capture negative ion mass spectrometry (GC/ECNI-MS). The single-chain Br-CP mixtures were obtained by the shared chlorination and bromination of eight single-chain alkanes (C10 to C17) at two reaction times, respectively. The carbon content of the 16 single-chain Br-CP products, determined by elemental analysis (EA), ranged from 30.8 to 43.8 %. The typical hump peak known from CPs was detected with GC with flame ionization detection (GC/FID), electron capture detection (GC/ECD) and GC/ECNI-MS. The complexity indicated that low-resolution mass spectrometry is not sufficient for an adequate analysis of Br-CPs. A mathematical formula was developed which allows to calculate all possible combinations of Br and Cl that are in line with the carbon content. The proton magnetic resonance spectroscopy (1H NMR) spectra showed similarities to the ones of CPs with one chemical shift range for protons on nonhalogenated carbons and one for protons with one halogen on the same carbon.